1986
DOI: 10.1104/pp.81.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Transport in Protoplasts Isolated from Soybean Leaves

Abstract: We isolated large quantities of mesophyll protoplasts from source and sink leaves of soybean plants and examined them for amino acid uptake. Accumulation of amino acids in isolated protoplasts was linear for at least 40 minutes. Uptake kinetics revealed the presence of both saturable and linear components. Increasing external pH decreases the uptake. The uncoupler, carbonyl cyanide p-trifluoromethoxyphenylhydrazone at 15 micromolar inhibited and fusicoccin at 10 micromolar stimulated amino acid uptake. Our dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The phenylpropanoid pathway leads to lignin biosynthesis suggesting, at least in part, the beginning of senescence. The low levels of glutamic acid and alanine in the vacuolar compartment (Table 2) and the high levels of glycine in chloroplast compartment (Table 2) may suggest low storage of nitrogen in leaves, and the ready export of amino acid metabolites, as it has been earlier reported that amino acids accumulation is greater in the sink than in the source in soybean leaves (VerNooy and Lin 1986).…”
Section: Metabolite Profiling 301mentioning
confidence: 87%
“…The phenylpropanoid pathway leads to lignin biosynthesis suggesting, at least in part, the beginning of senescence. The low levels of glutamic acid and alanine in the vacuolar compartment (Table 2) and the high levels of glycine in chloroplast compartment (Table 2) may suggest low storage of nitrogen in leaves, and the ready export of amino acid metabolites, as it has been earlier reported that amino acids accumulation is greater in the sink than in the source in soybean leaves (VerNooy and Lin 1986).…”
Section: Metabolite Profiling 301mentioning
confidence: 87%
“…Although these systems have provided important insight into the nature of amino acid transport, this experimental approach is limited by a number of problems which can compromise investigations of membrane bound transport systems. For example, rapid metabolism of the transported amino acid can lead to an overestimate of transport stoichiometries and metabolically linked feedback control systems may significantly influence transport activity (3,20,24). Furthermore, differential rates of accumulation by the various cell types present in an intact tissue and the existence of ill-defined diffusion barriers may further complicate interpretation.…”
mentioning
confidence: 99%
“…Amino acid transport in plants is frequently associated with accumulation against a significant free energy gradient across the plasma membrane. Several lines of evidence have linked this active transport process to the proton electrochemical difference generated by the plasma membrane proton-pumping ATPase (10, 13,15,20,[23][24][25] and recently, Bush and Langston-Unkefer (6) provided the first in vitro evidence demonstrating proton-amino acid symport activity in isolated plasma membrane vesicles.…”
mentioning
confidence: 99%
“…lism in a variety of plant systems (3,15 (13). We determined that chloramphenicol at 50 gg ml-' in the uptake and efflux media had no noticeable effect on uptake or passive efflux of aAIB, indicating that microbial contamination was not a problem in these relatively long-term experiments.…”
mentioning
confidence: 99%